La danza folklórica y su incidencia en el desarrollo psicoemocional en la E.E.B. Benigno Bayancela período 2022-2023 - Cabrera Deleg, Nayely Jhosmania (2023)
This research work is about Folkloric dance and its incidence in the psychoemotional development in the Benigno Bayancela School, academic period 2022-2023, the general objective was: To contribute with folkloric dance in the psychoemotional development of 7th grade students parallel "A" of the "Benigno Bayancela" School in the city of Loja, academic period 2022- 2023; likewise, the scientific, analytical, inductive, deductive and observational methods were used, and observational methods were used; a population of 22 human being was involved, which were 21 students to whom a survey and an interview directed to the teacher were applied, the purpose of the survey was to elucidate the problems investigated. Thus it was also determined that within the educational institution, folkloric dance is scarcely used as a means of expression or recreation, for this reason, this generates a lack of motivation, this generates demotivation in the students because they do not have an activity that provides them with new learning and challenges within their educational process. Therefore, it is concluded that students should be aware of their emotions, however, the way to express and manage them is complicated, which is why folkloric dance is a means that allows them to show their emotions, to know how to express that allows them to show them, and knowing how to effectively demonstrate each other is indispensable the factors that surround them are several and for a good understanding, a healthy environment is understanding requires a healthy and full environment. Keywords: Dance, Folklore, Psychology, Education, Emotions.